menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Given that f ( x ) = x 2 − 4 x − 12 f(x)=x 2 −4x−12 and g ( x ) = x − 6 g(x)=x−6, find ( f ⋅ g ) ( x ) (f⋅g)(x) and express the result in standard form.
asked
Mar 19, 2023
59.6k
views
15
votes
Given that
f
(
x
)
=
x
2
−
4
x
−
12
f(x)=x
2
−4x−12 and
g
(
x
)
=
x
−
6
g(x)=x−6, find
(
f
⋅
g
)
(
x
)
(f⋅g)(x) and express the result in standard form.
Mathematics
high-school
Roman Minenok
asked
by
Roman Minenok
4.4k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
6
votes
Answer:
(f⋅g)(x)=-4(x-6)-12
=-4x+24-12
=-4x+12
Rafff
answered
Mar 24, 2023
by
Rafff
5.5k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.2m
questions
6.7m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
I need to simplify this expression.
Need answer to math problem!!!
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org